Getting wrecked : women, incarceration, and the American opioid crisis - Sue, Kimberly (California series in public anthropology., 2019)
"Getting Wrecked provides a rich ethnographic account of women battling addiction as they cycle through jail, prison, and community treatment programs in Massachusetts. Since incarceration has become a predominant American social policy for managing the problem of drug use, including the opioid epidemic, this book examines how prisons and jails have attempted concurrent programs of punishment and treatment to deal with inmates struggling with a diagnosis of substance use disorder. An addiction physician and a medical anthropologist, Kimberly Sue powerfully illustrates the impacts of incarceration on women's lives as they seek well-being and better health while confronting lives marked by structural violence, gender inequity, and ongoing trauma"--Provided by publisher.